Understanding for whom, under which circumstances and how sedentary behaviour interventions for older adults work: a realist review - Greet Cardon; Sofie Compernolle; Geert Crombez; Sebastian Chastin; Delfien Van Dyck; Emelien Lauwerier; Laura Van de Velde; Femke De Meester; Fientje Mertens; Sanne Stegen (BMJ Open)
Objectives Reducing sedentary behaviour (SB) in older adults is a promising strategy to promote healthy ageing. However, to develop more effective interventions, more in-depth information is needed on how existing interventions work. The present realist review aims to identify the working mechanisms and contextual preconditions to guide the development of future interventions.Design A realist review was conducted following the iterative process of Pawson and Tilley and reported following the RAMESES publication standards.Data sources Evidence was searched in four databases: EMBASE, PubMed, Web of Science and Scopus, and in the grey literature.Eligibility criteria All study types and designs were included. Studies conducted in older adults with a mean age of 60 years or older, providing information on the context, mechanisms and/or outcomes of interventions aimed at the reduction of SB were eligible for inclusion and appraised for relevance and rigour.Data extraction and synthesis All data were coded by two independent reviewers. Sections that contained relevant information to refine, refute or confirm the initial programme theory were given a code. Based on these codes, context-mechanism-outcome configurations were made, and a final programme theory was developed.Results In total, 58 studies, from 61 articles, were eligible. The review revealed three important contexts for changes in SB: the (1) motivation, (2) opportunities and (3) capabilities of older adults. Depending on the context, other behaviour change techniques should be used to trigger specific mechanisms and, in turn, reduce SB. Especially, the impact of the underlying automatic processes of SB on the effectiveness of SB interventions became clear. Existing interventions primarily focus on the reflective processes guiding SB, without taking into account that SB is often an automatic response that occurs unconsciously, with little reasoning.Conclusions The effectiveness of SB interventions in older adults highly depends on the context in which the interventions occur. In particular, the context of automatic motivation should receive more attention to break the ingrained habit of SB in older adults.